A cross‐sectional survey of U.S. hospital pharmacy leaders on departmental initiatives to address burnout. Issue 6 (9th June 2020) - Bilhimer, Matt; Acquisto, Nicole M.; Slocum, Giles W.; Cocchio, Craig; Groth, Meghan; Rozycki, Elizabeth; Sturgill, Marc; Weant, Kyle; Bridgeman, Patrick
Abstract: Introduction: Burnout syndrome prevalence among hospital experience is increasingly described; however, no data explain how United States (U.S.) hospital pharmacy departments are addressing it. Objectives: This survey study sought to detect what strategies have been taken to prevent or address burnout. Methods: A customized, 19‐question descriptive survey was open for two, 1‐month periods in 2019. The survey addressed questions toward U.S. hospital pharmacy department leaders regarding leadership demographics, perception of burnout as a problem, and steps taken to address burnout. The first survey period was open to Directors of Pharmacy in the Vizient purchasing network and the second to members of three American Society of Health‐System Pharmacist's Connect Communities. Descriptive statistics are presented and Spearman rank‐order correlation was used for comparisons. Results: A total of 216 surveys were completed. Half of the participants were pharmacy directors, having worked less than 5 years in their position (n = 110, 50.9%). Eighty‐two percent believed their departments were negatively affected by burnout; however, only 53.7% formally assessed their employees. Twenty‐eight percent (n = 59) reported interventions to combat burnout have been instituted, whereas 26.2% had plans to initiate measures. The most frequent interventions implemented in each category were: communication (department meetings [98.3%], informal surveys [62.7%], management style changes [57.6%]), workflow (scheduling process changes [78%], technologies [72.9%], verification process changes [64.4%]), and quality improvement (stress reduction presentations [49.1%] and mealtime protections [40.7%]). Funding for interventions was from the annual budget (40.7%) or absent (42.4%). Directors of Pharmacy, management with longer job tenure, and those that had already implemented mitigation strategies were less likely to perceive that work performance is negatively impacted by employee burnout compared with others. Conclusion: Most participants acknowledge burnout may negatively impact their departments. Communication, workflow, and quality improvement strategies have been identified, albeit infrequently. Further study is warranted to continue investigating effective methods.